Makna Simbolik Gerak Tari Rejang Adat Tumbu pada Upacara Piodalan Ageng di Pura Batur Banjar Tumbu Kaler Karangasem, Bali - Ni Ketut Suryaningrum; Usrek Tani Utina (Dinasti Research, 2026)
The Rejang Adat Tumbu dance is a sacred dance unique to Tumbu Village. The Rejang Adat Tumbu dance is presented as a part of the Piodalan Ageng ceremony. This qualitative research aims to reveal the symbols that appear in the performance of the sacred dance during the Piodalan ceremony. Through phenomena arising from the Piodalan ceremony, the researcher employs ethnocoreology and Ferdinand de Saussure's semiotic theory. Data were obtained through participant observation, unstructured interviews, documentary studies, and literature reviews. These methods were conducted by the researcher with community figures and religious ceremony leaders at Pura Batur, Banjar Tumbu Kaler. The results of this study indicate that the Ngembat movements to the right and left have a dual meaning: spiritually, as a special symbol of welcome from the angels who dance to greet the sesuwunan and ancestors during the Piodalan Ageng ceremony, and philosophically, symbolizing the ancestors' persistence in weaving pandan mats as a means of the Piodalan ceremony. This performance is an adaptation of the Awig-awig of Tumbu Village, based on the teachings of Tri Hita Karana, which aim to maintain the balance of the universe. The symbols revealed are expected to serve as a foundation for the community of Tumbu Village, emphasizing the importance of sincerity and wholeheartedness in conducting the Piodalan Ageng ceremony.